The first population-based national tuberculosis prevalence survey in Ethiopia, 2010-2011 - Kebede, A H; Alebachew, Z; Tsegaye, F; Lemma, E; Abebe, A; Agonafir, M; Kebede, A J; Demissie, D; Girmachew, F; Yaregal, Z; Dana, F; Getahun, M; et al. (The international journal of tuberculosis and lung disease, 2014)
Tuberculosis (TB) remains a major public health problem in Ethiopia. To determine the prevalence of pulmonary TB among the general adult population aged ≥15 years in 2010-2011. METHOD A nationwide, cluster-sampled, stratified (urban/rural/pastoralist), cross-sectional survey was conducted in 85 selected clusters. All consenting participants were screened for TB using: 1) chest X-ray (CXR) and 2) an interview to screen for symptoms suggestive of TB disease. Of 51,667 eligible individuals, 46,697 (90%) participated in the survey and completed at least the screening interview. CXR was performed among 46,548 (99.7%) participants. A total of 6080 (13%) participants were eligible for sputum examination. From the survey, it was estimated that in the national adult population 1) the prevalence of smear-positive TB was 108/100,000 (95%CI 73-143), and 2) that of bacteriologically confirmed TB was 277/100,000 (95%CI 208-347). We found that the TB burden was lower than previously thought, which may indicate better programme performance. However, a high proportion of TB among young persons suggests that TB is circulating in the community and that there is a need for more efforts to limit the spread of TB disease.